EFFORTS MANAGEMENT OF CUTANEUS LARVA MIGRANS IN A 27-YEARS OLD FEMALE PATIENT THROUGH A FAMILY MEDICINE APPROACH AT MUARA BATU PRIMARY HEALTH CENTER, NORTH ACEH REGENCY - Raihannisa Anjani (Jurnal Medika Hutama, 2026)
Mrs. Patient. I, Female 27 years, came to the Muara Batu Health Center with complaints of itching in the stomach since 2 months and Heavy 1 last week. Complaints in the form of reddish spots that spread to form winding lesions (serpiginosa) accompanied by itching, especially at night. The patient works as a brick maker and often does not use footwear so that the risk of exposure to contaminated soil, and there is a history of similar complaints in the patient's child. Primary Data were obtained through alloanamnesis, physical examination, as well as home visits, filling in the family folder, and filling out patient files. The assessment is based on a holistic diagnosis of the beginning, process, and end of the visit in quantitative and qualitative terms. Management includes pharmacological therapy (albendazole and antihistamines) as well as education on personal hygiene, the use of footwear, and the Prevention of environmental exposure through a family medicine approach.